2022
DOI: 10.3748/wjg.v28.i16.1722
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “Artificial intelligence in gastroenterology: A state-of-the-art review”

Abstract: Colon capsule endoscopy (CCE) was introduced nearly two decades ago. Initially, it was limited by poor image quality and short battery time, but due to technical improvements, it has become an equal diagnostic alternative to optical colonoscopy (OC). Hastened by the coronavirus disease 2019 pandemic, CCE has been introduced in clinical practice to relieve overburdened endoscopy units and move investigations to out-patient clinics. A wider adoption of CCE would be bolstered by positive patient experience, as it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…These improvements in commonly used performance metrics have shown not to be affected by factors known to influence detection by the human eye, including the size and morphology of the lesions [ 19 ]. Artificial intelligence is expected to play a major role in improving the acceptability and the diagnostic yield of CCE [ 20 ]. These systems may help in several steps of the CCE process, from predicting the quality of colon cleanliness, lesion detection and the distinction of colorectal lesions [ 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These improvements in commonly used performance metrics have shown not to be affected by factors known to influence detection by the human eye, including the size and morphology of the lesions [ 19 ]. Artificial intelligence is expected to play a major role in improving the acceptability and the diagnostic yield of CCE [ 20 ]. These systems may help in several steps of the CCE process, from predicting the quality of colon cleanliness, lesion detection and the distinction of colorectal lesions [ 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Artificial intelligence is expected to play a major role in improving the acceptability and the diagnostic yield of CCE [ 20 ]. These systems may help in several steps of the CCE process, from predicting the quality of colon cleanliness, lesion detection and the distinction of colorectal lesions [ 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In general, the AI tools currently under development for digestive health care mainly aim to be assistive, guiding the clinical decision-making process. Many of the initial efforts have centred on automating the detection and diagnosis of colorectal neoplasia, highlighting the potential of AI applied to CE to identify and characterise lesions in colorectal cancer screening [60][61][62]. The initial explorations of AI algorithms to identify colorectal neoplasia in CE images had relatively modest sensitivity [63].…”
Section: Improved Efficiency Of Gastrointestinal Examinationsmentioning
confidence: 99%
“…However, following the impact of the recent COVID pandemic, an NHS Scotland evaluation demonstrated that the technology could lead to relieving the backlog in endoscopy on a national level. Still, CCE generates a video containing more than 50,000 images; this could be time-consuming and inefficient to analyse [ 2 , 3 ]. As a result, the advances in AI application on image analysis make AI-assisted CCE video analysis one of the most active research areas.…”
Section: Introductionmentioning
confidence: 99%